Middle Eastern and Islamic Influence on Western Art & Liturgy: Cultural Exchanges in Late Antiquity & the Middle Ages (American Journal of Islam and Society, 2004)
Central to the conference, held during March 5-6, 2004, at Trinity College,University of Toronto (Canada), was the desire of its organizer, AndrewHughes, to find analogies in other disciplines to his speculation that theEuropean plainsong (liturgical chant) of the Middle Ages was performed in a manner similar to that of Middle Eastern music (“Continuous Music:Natural or Eastern? The Origins of Modern Performance Style”). His speculationstemmed from decades of discussions with his colleague TimothyMcGee about the nature of musical sound. Oral transmission, its replacementby various difficult-to-interpret notations, and an often polemic rejectionof Arabic influence make the investigation difficult and controversial.1McGee responded (“Some Concerns about Eastern Influence in MedievalMusic”) and later, working from practical experiments presented by agroup of graduate students attending the conference, offered a very interestingnew interpretation. Some reservations were expressed by CharlesBurnett (Warburg Institute, London), a distinguished Arabist with musicologicalqualifications. He was invited to comment on the initial round tableand the conference as a whole.Other papers relevant to music were George Sawa’s review of Arabictheories of medieval music (“The Uses of Arabic Language in MedievalRhythmic Discourses”). He referred to numerous matters that might havea bearing on European music, especially with respect to ornamentationand rhythm. Art Levine discussed other non-western musical cultures,some of which were also influenced by Islamic music, and raised questionsabout ornamentation, tuning, and the nature of pitch (e.g., what is anote? “What Can Non-Western Music Offer?”).Moving from the sound of music to words about it, Randall Rosenfelddescribed numerous pilgrimage and Crusader chronicles. They containpassages reporting that Europeans found little strange in eastern music,suggesting that eastern and western music cannot have been as dissimilaras seems to be the case today (“Frankish Reports of Central Asian andMiddle Eastern Musical Practice”). John Haines traced in detail the use ofArabic terms from Adelard of Bath’s twelfth-century translation ofEuclid’s geometrical writings to an important mid-thirteenth-centurymusical treatise, where the terms for quadrilateral shapes resemblingsquare notation are used to refer to musical symbols (“Anonymous IV’sElmuahim and Elmuarifa”). Luisa Nardini presented details of particularmelodic characteristics in Gregorian chants that identify Byzantine andGallican melodies in Gregorian repertories (“Aliens in Disguise:Byzantine and Gallican Songs as Mass Propers in Italian Sources”).In other disciplines, Philip Slavin revealed the striking similarities oftopics and words between Byzantine and Roman (Gregorian) penitentialliturgy, seeing possible origins in Jewish prayers and the fourth-centuryConstitutiones Apostolorum (“Byzantine and Western Penitential Prayers ...